Is it safe to perform adenotonsillectomy in children with Down syndrome? - BİNNETOĞLU, ADEM; YUMUŞAKHUYLU, ALİ CEMAL (SPRINGER, 2016)
This retrospective review aims to evaluate the postoperative morbidity and mortality of 30 patients with Down syndrome who underwent adenotonsillectomy between June 2012 and December 2015 in a tertiary referral center. Mean age was 7.8 with a range of 3-12. There were 20 (66.6 %) male and ten (33.3 %) female patients. Mean follow-up was 23 months with a range of 7-43 months. 23 (76.6 %) of 30 patients had been operated due to obstructive tonsillar and adenoid hypertrophy, whereas seven (23.3 %) of them operated for chronic recurrent infections. All of the patients had undergone adenotonsillectomy operation; one patient had also bilateral tympanostomy tube insertion. Hospital stay was noted 1.3 days in average with a range of 1-3 days. Anesthetic complications of persistent bradycardia and postextubation respiratory difficulty occurred in two (6.6) patients. Patient who had intraoperative bradycardia necessitated intensive care unit stay and pacemaker implantation during follow-up. 3 (10 %) patients had late onset hemorrhage between days 7 and 10 and required intraoperative bleeding control. We did not experience any other morbidity and mortality except the abovementioned ones. In conclusion, adenotonsillectomy in patients with Down syndrome is a worthwhile operation with certain risks and these operations should better be performed by the tertiary referral centers which have the capacity to deal with the complications.
Keywords: Down syndrome; Tonsillectomy; Adenoidectomy; Complication; Bradycardia; Obstructive sleep apnea; OBSTRUCTIVE SLEEP-APNEA; AIRWAY-OBSTRUCTION; ADENOIDECTOMY; TONSILLECTOMY; SEVOFLURANE; INSTABILITY; TRISOMY-21; INDUCTION; PATTERNS